Short Communication: Sex types in flowering of Jatropha curcas - DASUMIATI DASUMIATI; MIFTAHUDIN MIFTAHUDIN; TRIADIATI TRIADIATI; ALEX HARTANA (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Dasumiati, Miftahudin, Triadiati T, Hartana A. 2017. Short Communication: Sex types in flowering of Jatropha curcas. Biodiversitas 18: 275-279. Commonly, Jatropha curcas ( jatropha) produces male and female flowers in the different flower. But, the other jatropha have male and hermaphrodite flowers in the different flower. The combination of those flowers in one plant causes sex differentiation in jatropha. This study aimed to identify the sex types of flowers and plant in jatropha, as well as to know the stability of sex types after stem cuttings propagation. The survey was conducted to the population of jatropha in Cikampek, Karawang and Pakuwon, Sukabumi, West Java, Indonesia. We found three sex types in both plantations: monoecious that have male and female flowers, andromonoecious that have male and hermaphrodite flowers, trimonoecious that have male, female, and hermaphrodite flowers in the same plant. Andromonoecious and monoecious jatropha have stable sex type, but trimonoecious jatropha has unstable sex type. The stability of sex type is related to the number of primary branch and distance between nodes. Keywords: Andromonoecious, Jatropha curcas, monoecious, trimonoecious